Assessment of diagnosis and treatment practices of diarrhoea in children under five in Maputo-Mozambique - Nórgia Elsa Machava; Elsa Maria Salvador; Fhumulani Mulaudzi (Elsevier, 2022)
Background: Although diagnosis and treatment of diarrhoea are considered easy, statistics show that 525,000 children worldwide die annually due to diarrhoea, 90% of the deaths are in Sub-Saharan Africa and South Asia, and Mozambique account for 6.9%. Assessment of practices of diagnosis and treatment of diarrhoea in children under five were con-ducted in Maputo, Mozambique. Design and method: The study was retrospective - source of information: record books from 2015 to 2019. All statements about age, gender, signs and symptoms, diagnoses, and treatment were collected to assess practices implemented by the health professionals to diagnose diarrhoea in children under five. Results: A total of 9,041 cases were found, where 4,052 (44, 8 %) were female, urban area accounts for 7,668 (74.8 %). Children younger than 6 months 1,013 (11,2%); from 6 to 11 months 1,370 (15,2%); from 12 to 23 months 2,535 (28 %); from 24 to 35 months 1,674 (18.5 %), from 36 to 47 months 1,239 (13.7 %) and from 48 to 59 months 1,210 (13.4 %). About 3,644 (40.3 %) had fever, 3,467 (38 %) vomit, 1,999 (22 %) blood in stool and other symptoms; only 5 (1 %) of the children's stools were submitted for laboratory analysis. The clinical diagnoses were diarrhoea 3,905 (43 %), diarrhoea and vomit 2,037(22 %) and others. The main treatment was oral rehydration salts 7,118 (79 %) and 21 % antibiotics. Conclusion: Even when the signs and symptoms (fever and blood in stool) suggested or required laboratory exams, this was not done. Nevertheless, the children were treated with antibiotic without the screening of etiological agent.